Crossword Puzzle Games to Enhance Students' Vocabulary Mastery - Ira Rafsanjani Shohib (Retain: Journal of Research in English Language Teaching, 2024)
The first language skill that must be mastered when learning English is vocabulary. Vocabulary mastery is still lacking because their curiosity is still low and they consider learning vocabulary uninteresting and not very important in learning. This research aims to find out whether the use of the learning media "Crossword Puzzle Game" is effective in increasing the vocabulary mastery of class X students at MAN 1 Gresik. This research applied a collaborative action research design in collaboration with one of the English teachers. For data collection, this research used pre-tests, post-tests, and interviews. The data obtained was analyzed using SPSS (Statistical Package for Social Science). The results of this research are that the mean student score in the pre-test is 41.90 and the mean student score in the post-test is 76.67. The students' mean post-test score was higher (34.77) than the pre-test. This shows that the use of crossword puzzles increases students' vocabulary significantly. The results of the normality test in this study show that the data is normal which is supported using a paired sample test to test the hypothesis. The results of the paired sample test are Asymp. sig. 2-tailed pre-test and post-test probability values of 0.000. This value is lower than alpha ? 0.05, This means that the research hypothesis is approved. In interviews with students to find out students' perspectives on their experiences in using crossword puzzle game media which can improve vocabulary mastery. They said that by getting used to seeing or recognizing the new vocabulary they encounter; it will be easier for them to remember the vocabulary and make learning English vocabulary effective and enjoyable. Based on the results above, it show that using "Crossword Puzzle Game" can help students improve vocabulary mastery.